Knowledge in Management of Directors and Chiefs and the Relationship with their Biosociocultural Factors - Chancahuaña, Percy Angel (2019)
The health sector is currently undergoing a poor situation in the management of its resources because managers do not know and do not apply the administration as a fundamental piece for their performance in the position, a situation that brings as consequence the non-fulfilment of the objectives and goals, interpreted as institutional failure. It is important that the manager responsible for directing a public or private entity have knowledge in administration, requirement that should be considered indispensable before designating a position of director or chief. the research was aimed at determining the level of knowledge in administration of directors and heads of the network of health Huaylas South and the relationship that exists with their Biosociocultural factors, so the observational, cross-sectional, descriptive, correlational method was used, the institution where the research was carried out was the Southern Huaylas Health Network, where we found 86% of the directors and managers had a level of knowledge in middle management, which have significant relationship with the variables training in administration, working condition and educational level, in conclusion these last three Variables are factors that determine a level of knowledge, the higher the academic level and the more trainings the manager receives, he will elevate his knowledge in administration and using the scientific method.